Analysis of Broadband Seismic Recordings of Landslide Using Empirical Green's Function. Issue 9 (6th May 2019) - Zhang, Zhen; He, Siming
Abstract: The 2010 Mount Meager landslide generated strong seismic waves. We used seismic signals generated by a smaller landslide that occurred within 2 min of the end of the main landslide as the empirical Green's function (EGF) with which to obtain landslide dynamics from high‐frequency signals. We then obtained the apparent force‐time function of the landslide based on the EGF by inverting the higher‐frequency seismic signals. The apparent force‐time function shows that the source material of the main landslide came from four collapses and that the second collapse involved multiple small collapses. We also used the EGF to simulate the vertical seismogram recorded at one station and found that the synthesized seismogram fits the response of the bulk mobilization of the sliding materials remarkably well. Our study demonstrates that the use of the EGF can significantly broaden quantitative insights into landslide dynamics. Plain Language Summary: Seismic records reflect the effects of landslide dynamics and the path of seismic waves through the Earth. Because the calculation of the high‐frequency component of the effect of a wave's path through the Earth requires a detailed characterization of the velocity and attenuation structure, the effects of landslide dynamics can only be estimated by inverting the long‐period seismic signals. To study the high‐frequency seismic signals generated from the Mount Meager landslide, we considered the seismic signals generated by a smaller landslide as the effects of the path of seismic waves. We used the seismic signals generated by the smaller landslide to simulate the signal generated by the main landslide to overcome the effects of a potential overlap in the frequency domain between signals from the bulk and those from smaller particles. Our results show that the seismic signals generated by a small landslide can be used to improve our understanding of those generated by the main landslide. Key Points: The empirical Green's function was used to invert the apparent force‐time function of a landslide The dynamic properties of the landslide were estimated from high‐frequency signals The potential overlap in the frequency domain between signals from the bulk and those from smaller particles was analyzed